Karakteristik Suhu dan Produksi Gas dengan Variasi Laju Input Udara pada Proses Gasifikasi Tandan Kosong Kelapa Sawit Menggunakan Inverted Downdraft Gasifier - , ASIH PRIYATI, Dr. Ir. Bambang Purwantana, M.Agr. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
In this study, temperature and gas producer flowrate in pyrolysis proses of oil palm empty fruit bunches were investigated using inverted downdraft gasifier with capacity 0,113 m3. Experiment was conducted by measure the superficial velocity as the most important measure of its performance. The effect of air flowrate inlet were investigated at 13,08lpm, 18,24lpm, 41,04lpm, 115,56lpm and 191,61lpm by varied blower nozzle outlet. causes SV at 4,69m/s, 7,64m/s, 17,87m/s, 42,3m/s, dan 65,77m/s. The operation results airflow inlet influences to supervicial velocity, process time, air fuel ratio, production gas flowrate, fuel consumption flowrate, yields of charcoal and tars. A low SV was obtained with the lower air flowrate, causes relatively slow pyrolisis conditions, produces high yields of charcoal, large quantities of tars, and gas with high methane content. A high SV causes very fast pyrolisis, producing less charcoal and tars, and gas with less methane content. Further studieswith the same fuel was recommended using SV at range 4,69m/s to obtained specific results for pyrolysis process.